2018
DOI: 10.18352/ijc.828
|View full text |Cite
|
Sign up to set email alerts
|

Exploring governance structures of high altitude rangeland in Bhutan using Ostrom’s Design Principles

Abstract: High altitude rangeland and livelihood systems in Bhutan are undergoing changes in resource availability, population and user rights. This paper explores the existing governance structures of high altitude rangelands in Bhutan using Ostrom's design principles as a framework for analysis. Qualitative interviews and focus group discussions were used to capture perceptions of 151 herders, sedentary livestock farmers and government officials across three case study sites. The research showed that most high altitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…The Land Act of 1979 and the Forest and Nature Conservation Act of 1995 devolved grazing rights on grassland to individuals and communities, but lacked provisions to clarify ownership and rangeland management activities allowing sustainable use (Moktan et al 2008;Ura 2002). The Land Act of Bhutan 2007 was seen as a policy shift toward the inclusion of management and provisioning in the bundle of rights (eg leasing) of tsamdrog property rights, but its perception by herder communities attached to traditional rules led to confusion and anxiety (Tenzing et al 2017a(Tenzing et al , 2017b. found that local knowledge and traditional practices have a role to play in avoiding land degradation and that granting of management rights is vital to encouraging rangeland maintenance activities.…”
Section: Collaborative Modeling and Simulation To Mitigate High-eleva...mentioning
confidence: 99%
“…The Land Act of 1979 and the Forest and Nature Conservation Act of 1995 devolved grazing rights on grassland to individuals and communities, but lacked provisions to clarify ownership and rangeland management activities allowing sustainable use (Moktan et al 2008;Ura 2002). The Land Act of Bhutan 2007 was seen as a policy shift toward the inclusion of management and provisioning in the bundle of rights (eg leasing) of tsamdrog property rights, but its perception by herder communities attached to traditional rules led to confusion and anxiety (Tenzing et al 2017a(Tenzing et al , 2017b. found that local knowledge and traditional practices have a role to play in avoiding land degradation and that granting of management rights is vital to encouraging rangeland maintenance activities.…”
Section: Collaborative Modeling and Simulation To Mitigate High-eleva...mentioning
confidence: 99%
“…The lesson learned was that donor projects could have some influence at a local level on granting management rights, but only within the prevailing leasing and decisionmaking systems, which were beyond their control. Until implementation of the national lease reallocation is finalized, herders are reluctant to make improvement decisions (Tenzing et al 2018).…”
Section: Savings Schemes and Livelihood Impactsmentioning
confidence: 99%
“…Under new leasing arrangements, herders will be permitted to grow improved pasture and manage grasslands if they develop a management plan. However, a lack of practical leasing implementation over the last decade has fueled confusion and uncertainty among herders (Gyeltshen et al 2010;Tenzing et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While much has been written about conflicts among pastoralists in Africa (Adano et al 2012;Hagmann and Mulugeta 2008) and about farmer-herder conflicts in Africa (Moritz 2010;Kuusaana and Bukari 2015;Brottem 2016), the literature on the same topics for the Central Asian and Caucasus regions is scarce. Although pasture use is prevalent in this region (Kerven 2006), authors touch only marginally on the issue of conflict as a part of studies about pasture governance (Upton 2009;Tenzing, Millar, and Black 2018;Vanselow, Kraudzun, and Samimi 2012). This paper aims to fill this gap by explicitly investigating conflicts about pasture resources in the Caucasus region.…”
Section: Introductionmentioning
confidence: 99%